Combined XPS and contact angle studies of flat and rough ethylene-vinyl acetate copolymer films - Doganci, M. D.; Cansoy, C. E.; Ucar, I. O.; Erbil, H. Y.; Mielczarski, E.; Mielczarski, J. A. (Wiley-Blackwell, 2012)
Flat and rough thin films were prepared by dip coating using LDPE, PVAc, and EVA polymers containing 1240% VA contents. Surface free energy of flat films was determined by measuring contact angles. Surface atomic composition was investigated by XPS at 0 degrees and 60 degrees take-off angles. XPS results show that hydrophobic PE component was found to enrich at the near-surface region for all EVA samples for a depth of similar to 5 nm for both flat and rough surfaces, whereas hydrophilic VA component was enriched on the surface when VA < 18% for only at 10 nm depth. The difference between the XPS results of the flat and rough surfaces was not significant for EVA samples except EVA-33 surface where the atomic oxygen content decreased 15-20% for rough surfaces. Contact angle hysteresis values for the rough samples were much larger than that of the flat samples for LDPE and EVA-12 surfaces due to the presence of partial trapping of air pockets on these rough surfaces. A good agreement was obtained between surface concentration of atomic oxygen in the 5 nm outermost layer and gamma S- surface free energy component especially for the samples having high VA contents. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: ethylene-vinyl acetate copolymers; contact angle; XPS; surface free energy; polyolefin